Reflective Teaching of EFL Instructors at Shambu College of Teacher Education - Moti Alemayehu Dheressa (Universitas Pendidikan Mandalika, 2022)
Being reflective is one of the most paramount capabilities that instructors need to be ready with post-method technology for their professional growth and development. The present study aimed to discover reflective teaching from extraordinary views in phrases of a) determinants that simulate instructors to reflect, b) outcomes that instructors revel in due to their reflective teaching, and c) boundaries that can get up and prevent instructors from reflective teaching. A qualitative data approach was hired to accumulate records from 10 EFL instructors triangulating semi-structured interviews, diaries, journals, and observations. Data analysis through thematic analysis is used for this to take a study. The results revealed that tinstructors not only reflect to respond to a problem, but additionally they reflect on diminishing some negative elements like strain or tension on the part of each trainees and themselves in addition to improving, enhancing, or mending something in teaching or studying. The codes of determinants have been additionally conceptualized into three large categories of reflection-in-action, reflection-on-action, and reflection-for-action, with the reflection-for-action, used more regularly by using the instructors. In the case of effects, the codes were labeled into classes of inner and outside outcomes. It was also concluded that some of the results reinforce the reflective teaching and play the role of determinants motivating instructors to reflect again. Regarding the boundaries, after categorizing the codes into external and internal boundaries, it was observed that external factors are more robust.